A second-order nonlinear optical crystal of molybdenum dioxide dichloride and its preparation and application
The MoO2Cl2 crystal assembled through the ‘pure FM’ strategy solves the problems of SHG effect and insufficient optical band gap of existing infrared nonlinear optical crystal materials, and realizes efficient laser frequency conversion and wide transmission range, with broad application prospects.
Patent Information
- Application Number
- CN202311005443.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-10
AI Technical Summary
Existing infrared nonlinear optical crystal materials have shortcomings in SHG effect and optical band gap, limiting their output power and wide application in laser applications.
The efficient transition metal oxygen halogen polyhedron NLO high-efficiency module was used to assemble the 'pure FM' strategy, disperse the redundant charge through halogenation and polymerization, and assemble the filler-free structure in combination with van der Waals force to prepare MoO2Cl2 crystals.
It has achieved a large SHG effect and a wide transmission range of molybdenum dichloride dioxide crystal in the infrared band, and the frequency doubling effect reaches 2.1 times that of KTiOPO4, and is suitable for laser frequency conversion and other fields.
Smart Images

Figure CN117127259B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystal materials and relates to a molybdenum dioxide dichloride second-order nonlinear optical crystal and preparation and application thereof. Background Art
[0002] Infrared second-order nonlinear optical crystals can achieve laser frequency conversion in the infrared band through nonlinear optical (NLO) processes such as difference frequency and optical parametric oscillation, and therefore are of great significance in advanced optical technologies such as remote sensing, medical surgery, and medical imaging. 2 ), silver gallium selenide (AgGaSe 2 ) and zinc germanium phosphate (ZnGeP 2 ) exhibit large second harmonic generation (SHG) effects, but these crystals have small optical band gaps. In contrast, metal oxide infrared nonlinear optical crystal materials generally have wider optical band gaps, which in principle can increase the output power of lasers. However, the small SHG effect of most oxide infrared nonlinear optical crystals limits their widespread application. Therefore, the development of metal oxide nonlinear optical crystals with large SHG effects in the infrared band is still challenging. Summary of the invention
[0003] The purpose of the present invention is to provide a molybdenum dioxide dichloride second-order nonlinear optical crystal and its preparation and application, so as to solve the current problem of lack of practical mid-infrared nonlinear optical crystal materials.
[0004] According to the module-filler model, the structure of a nonlinear optical crystal consists of a functional module (FM) and a filler, where the optical properties are mainly determined by the functional module and the filler balances the charge and regulates the structure. 4 (KTP) [TiO 6 ] 8- / [PO 4 ] 3- The anions are FM, K +Cations are fillers. Filler-free NLO crystals composed only of NLO efficient FMs can maintain kinetic and thermodynamic stability. In principle, removing fillers can increase the density of FMs, thereby optimizing optical nonlinearity. Based on this, the present invention proposes a "pure FM" strategy to assemble FM dense structures. The target structure is constructed by well-arranged NLO efficient modules of oxygen-halide polyhedrons centered on transition metals. The implementation of this strategy includes the following three key steps: (i) Selecting efficient FMs. FMs with large distortion are a prerequisite for constructing compounds with large SHG effects. Therefore, d 0 -TM center polyhedron is an ideal FM. (ii) Halogenation and polymerization of FM. The halogenation and polymerization of TM center polyhedron can effectively disperse redundant charges, thereby constructing an electrically neutral structure in the absence of fillers. More importantly, the halogenated FM exhibits more excellent microscopic optical properties, and the polymerization of these heteroanions is more conducive to maximizing the FM density in the target structure. (iii) Assembling secondary structures through van der Waals forces. Halogens can act as structural "scissors" in the structure, which can achieve dimensionality reduction of covalent structures. The resulting secondary structures (zero-dimensional clusters, one-dimensional chains and two-dimensional layers) can be assembled into filler-free structures through van der Waals forces. Compared with ionic bonds or covalent bonds, van der Waals forces shorten the distance between adjacent secondary structures and can eliminate undesirable dipole-dipole interactions, thereby minimizing the probability of the compound crystallizing in a central symmetric space group. According to the above strategy, the present invention successfully prepared van der Waals crystals of MoO 2 Cl 2 The crystal exhibits a strong SHG response (the SHG effect is 2.1 times that of KTP under 2100nm fundamental frequency light irradiation, which is the maximum value among transition metal oxyhalides), a wide transmission range (430 to 4537nm) and sufficient birefringence (0.35@2100nm).
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention provides a second-order nonlinear optical crystal of molybdenum dioxide dichloride, whose chemical formula is MoO 2 Cl 2 , belongs to the orthorhombic system, its space group is Fmm2, and the unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is
[0007] The crystal structure of molybdenum dioxide dichloride of the present invention is as follows: Van der Waals crystal MoO 2 Cl 2 By chlorinated [MoO4 Cl 2 ] modules, and the two-dimensional [MoO 2 Cl 2 ] ∞ Functional layer is the characteristic. MoO 2 Cl 2 The smallest asymmetric unit of [MoO] is composed of a crystallographically independent Mo, an O, and a Cl atom. The coordination sphere of each central Mo atom consists of four equatorial O atoms and two dipolar Cl atoms. 4 Cl 2 ] Octahedron presents C 2 Distortion. 4 Cl 2 ] octahedrons aggregate in the (100) plane to form a two-dimensional [MoO 2 Cl 2 ] ∞ These [MoO 2 Cl 2 ] ∞ The layers are further stacked along the a-axis to form the final three-dimensional structure under the action of van der Waals forces.
[0008] The second technical solution of the present invention provides a method for preparing a molybdenum dioxide dichloride second-order nonlinear optical crystal, comprising the following steps:
[0009] (1) mixing a molybdenum source, a chlorine source and a flux to form an initial mixed raw material;
[0010] (2) The initial mixed raw materials are placed in a closed hydrothermal reactor, heated for crystallization, and cooled to room temperature to obtain the target product.
[0011] Furthermore, the molybdenum source is molybdenum pentachloride.
[0012] Furthermore, the chlorine source is molybdenum pentachloride or aluminum chloride.
[0013] Furthermore, the flux is phosphorus pentoxide. In the reaction, the flux can lower the melting point of the mixed raw materials, and the synthesized molybdenum dioxide dichloride nonlinear optical crystal material does not contain phosphorus.
[0014] The present invention selects a sealed hydrothermal reactor as a container for chemical vapor deposition reaction, and the selected raw materials all have low melting / boiling points. During the heating reaction process, there is a difference between the actual temperatures of different parts of the hydrothermal reactor, and the reaction product and the substrate can be separated from different parts of the hydrothermal reactor.
[0015] Furthermore, the molar ratio of molybdenum, oxygen and chlorine in the initial mixed raw material is 1:(0.5-40):(0.5-40). Preferably, the molar ratio of molybdenum, chlorine and oxygen is 1:(5-20):(5-20).
[0016] Further, the heating temperature for crystallization is 200-240° C., and the crystallization time is not less than 24 hours. Preferably, the heating temperature is 220-230° C., and the crystallization time is not less than 48 hours.
[0017] Furthermore, in step (2), the cooling rate is 0.5 to 15°C / h. Preferably, the cooling rate is 0.5 to 5°C / h.
[0018] The third technical solution of the present invention provides an application of a second-order nonlinear optical crystal of molybdenum dioxide dichloride, which is used for frequency conversion output of visible mid-infrared laser. The molybdenum dioxide dichloride crystal material has a large frequency doubling effect. Under 2100nm laser irradiation, its powder frequency doubling effect is about KTiOPO 4 The band gap of the crystal material is 2.88eV, the optical transmission range is 430-4537nm, and the thermal stability temperature is 80℃. Therefore, the crystal material has broad application prospects in the field of nonlinear optics.
[0019] A fourth technical solution of the present invention provides an application of a molybdenum dioxide dichloride second-order nonlinear optical crystal in a frequency doubling generator, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The present invention provides a new inorganic crystal material, molybdenum dioxide dichloride, which has a large frequency doubling effect and is about KTiOPO under 2100nm laser irradiation. 4 The crystal frequency doubling intensity is 2.1 times, which can achieve type I phase matching. In addition, the crystal material has a wide transmission range in the visible light region and infrared light region, with a band gap of 2.88eV and an optical transmission range of 430-4537nm. It has broad application prospects in the fields of laser frequency conversion, photoelectric modulation, and laser signal holographic storage.
[0022] (2) The present invention provides a method for preparing the molybdenum dioxide dichloride crystalline material, which adopts a chemical vapor deposition method with mild reaction conditions and reacts at a temperature of 200 to 240° C. to obtain a high-purity crystalline sample with high yield. The method is simple and the conditions are mild, which is conducive to large-scale industrial production.
[0023] (3) The molybdenum dioxide dichloride crystal material of the present invention can be applied to a laser frequency converter, and can be used to output an infrared laser beam as a doubled frequency harmonic. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the crystal structure of molybdenum dioxide dichloride;
[0025] Figure 2 This is the Rietveld powder refinement spectrum of sample 1#;
[0026] Figure 3 is the UV-Vis-IR transmission spectrum of sample 1#;
[0027] Figure 4 is the infrared spectrum of sample 1#;
[0028] Figure 5 This is the thermogravimetric analysis spectrum of sample 1#;
[0029] Figure 6 Sample 1# and KTiOPO 4 Second harmonic signal diagram for samples in the range of 105 to 150 μm;
[0030] Figure 7 This is the second harmonic phase matching diagram of sample 1# in the 2100μm band. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0032] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0033] Embodiment 1:
[0034] Chemical vapor deposition synthesis of samples
[0035] The molybdenum source, chlorine source and flux are mixed in a certain proportion to form the starting raw materials, sealed in a hydrothermal reactor with a polytetrafluoroethylene lining, heated to the crystallization temperature, and after a period of constant temperature, the temperature of the reaction system is slowly lowered to room temperature at a certain rate, and transparent yellow block-like molybdenum dioxide dichloride crystals can be obtained on the upper part of the polytetrafluoroethylene lining.
[0036] The relationship between the type and ratio of raw materials in the initial mixture, crystallization temperature, crystallization time and sample number is shown in Table 1.
[0037] Table 1 Correspondence between samples, raw materials and synthesis conditions
[0038]
[0039]
[0040] Example 2
[0041] Crystal structure analysis
[0042] The structures of samples 1# to 6# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0043] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The crystal size is 0.15×0.17×0.05mm 3 ; The data collection temperature is 293K, and the diffraction light source is graphite monochromatized Mo-Kα rays The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-14 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.
[0044] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current were 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit were 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range was 10–70°, and the scanning step was 0.02°.
[0045] Among them, the single crystal X-ray diffraction test results show that samples 1#~6# have the same chemical formula and crystal structure, and the chemical formula is MoO 2 Cl 2 , molecular weight is 198.84, belongs to the orthorhombic system, its space group is Fmm2, and the unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is
[0046] Take sample 1# as a typical example, its crystal structure data is α=β=γ=90°, Z=4, the unit cell volume is Its crystal structure is Figure 1 shown.
[0047] The Rietveld refinement of XRD data showed that the experimental values fit well with the theoretical simulation values in the XRD refinement spectra of samples 1# to 6#.
[0048] Take sample 1# as a typical example. Figure 2 shown. Figure 2 The data points obtained by X-ray diffraction test after grinding sample 1# into powder are well fitted with the XRD curve simulated according to the crystal structure analyzed by its single crystal X-ray diffraction, indicating that the obtained sample has high purity.
[0049] Example 3
[0050] UV-Vis-NIR and IR transmission spectroscopy testing
[0051] The UV-Vis-NIR transmission spectrum test of sample 1# was conducted on a Cary 5000 UV-Vis-NIR spectrophotometer from Agilent Technologies, USA. Figure 3 As shown by the black line, Figure 3 The black line shows that the compound has no obvious absorption in the range of 430nm to 2500nm. The optical band gap of the compound is 2.88eV.
[0052] The infrared transmission spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 3 As shown by the gray line, Figure 3 The middle gray line shows that the compound has no obvious absorption in the range of 2500nm to 4537nm.
[0053] Example 4
[0054] Infrared spectrum test
[0055] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown, Figure 4 The characteristic absorption peaks of Mo-Cl bonds and Mo-O bonds indicate the existence of Mo-Cl bonds and Mo-O bonds in the sample.
[0056] Example 5
[0057] Thermogravimetric testing
[0058] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 5 As shown by Figure 5It can be seen that the compound is stable up to 80°C.
[0059] Example 6
[0060] Frequency doubling test experiment and results
[0061] The frequency doubling test experiment of sample 1# is as follows: a Q-switched Ho:YAG solid laser with a wavelength of 2100nm is used as the fundamental frequency light to irradiate the tested crystal powder, a photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. 4 The crystals were ground separately and sieved with standard sieves to obtain crystals of different particle sizes, with the particle size ranges of 26-50, 50-105, 105-150, 150-200, and 200-280 μm. The trend of the frequency-doubled signal intensity changing with the particle size was observed to determine whether phase matching could be achieved. 4 The second harmonic intensity generated by the sample can be used to obtain the relative size of the sample's frequency doubling effect.
[0062] The test results show that the compound molybdenum dioxide dichloride crystal has a large frequency doubling effect. Under 2100nm wavelength laser irradiation, the frequency doubling signal intensity is the control sample KTiOPO 4 2.1 times of the crystal (such as Figure 6 ), which can achieve type I phase matching (such as Figure 7 ).
[0063] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A second-order nonlinear optical crystal of molybdenum dioxide dichloride, characterized in that: Its chemical formula is MoO2Cl2, it belongs to the orthorhombic system, its space group is Fmm2, and its unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is The second-order nonlinear optical crystal is prepared by the following method: (1) mixing a molybdenum source, a chlorine source and a flux to form an initial mixed raw material; (2) placing the initial mixed raw materials in a closed hydrothermal reactor, heating and crystallizing, and cooling to room temperature to obtain the target product; The molybdenum source is molybdenum pentachloride; The chlorine source is one or a combination of molybdenum pentachloride and aluminum chloride; The flux is phosphorus pentoxide; The molar ratio of molybdenum element, oxygen element and chlorine element in the initial mixed raw material is 1:(0.5-40):(0.5-40); The temperature of heating crystallization is 200-240°C, and the crystallization time is not less than 24h; The cooling rate is 0.5~15℃ / h.
2. The method for preparing a molybdenum dioxide dichloride second-order nonlinear optical crystal according to claim 1, characterized in that: The following steps are involved: (1) mixing a molybdenum source, a chlorine source and a flux to form an initial mixed raw material; (2) placing the initial mixed raw materials in a closed hydrothermal reactor, heating and crystallizing, and cooling to room temperature to obtain the target product; The molybdenum source is molybdenum pentachloride; The chlorine source is one or a combination of molybdenum pentachloride and aluminum chloride; The flux is phosphorus pentoxide; The molar ratio of molybdenum element, oxygen element and chlorine element in the initial mixed raw material is 1:(0.5-40):(0.5-40); The temperature of heating crystallization is 200-240°C, and the crystallization time is not less than 24h; The cooling rate is 0.5~15℃ / h.
3. The use of a molybdenum dioxide dichloride second-order nonlinear optical crystal as claimed in claim 1, characterized in that: The second-order nonlinear optical crystal is used for frequency conversion output of visible and mid-infrared lasers.
4. Application of the molybdenum dioxide dichloride second-order nonlinear optical crystal as described in claim 1 in a frequency doubling generator, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.
Citation Information
Patent Citations
Compound potassium molybdenum phosphate, potassium molybdenum phosphate nonlinear optical crystal, and preparation method and application thereof
CN113668055A
Oxyhalide precursors
CN114174216A